Pengaruh Intensitas Bermain Video Game Online PUBG Dan Motivasi Untuk Mengikuti Kuliah Terhadap Prestasi Akademik Mahasiswa Di Kampus - Purnama Sari, Devi; Naryoso, Agus (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
Based on data obtained from the UNDIP technical dean related to the list of IP and IPK of 2016 Undip Engineering’s students, of which from 743 students in several departments, there were still 181 students or 24.35% who still got a GPA below 2.75 (standard try trying 2). High intensity in online games can give negative results to student academic achievement. However, motivation is one of the factors needed to support academic achievement. This study aims to determine whether there is an intensity of influence on playing PUBG online video games and the motivation to attend classes on student academic achievement on campus by using the concept of Internet Addiction and Two Factor Motivation Theory. The sampling technique uses nonprobability sampling which is done by purposive sampling with a total sample of 50 people with the criteria of undip engineering students of 2016 who play PUBG online video games. This test is carried out using a Simple Linear Regression Test. The results of this study indicate that there is a significant negative effect on the intensity of playing PUBG online video games on student academic achievement that is equal to 11.2%. The remaining 88.8% is influenced by other factors not examined in this study. Whic is the Correlation between variables is 0.017. This shows that the intensity of playing PUBG online video games affects student academic achievement on campus. That the higher the intensity in playing PUBG online video games, the lower the academic achievement of students on campus. The results of this study also showed that there was a very significant effect of motivation to attend college on student academic achievement on campus by 21.6%. The remaining 78.4% is influenced by other factors that not examined in this study. Correlation between variables shows significance is 0.001. This shows that there is a very significant effect on the intensity of playing PUBG online video games to student academic achievement campus. So, the higher the motivation in attend lectures, the higher the academic achievement. For further research, it is expected to be able to multiply more about other factors beyond the factors studied which can affect student academic achievement.